Training geological practice in Crimea: modern state, problems, ways of development - A. V. Turov (Известия высших учебных заведений: Геология и разведка)
Proved the uniqueness of the educational geological polygon located at the confluence of the Kacha and Alma (southwest Crimea). Consider the organization of training geological practice second course of MGRI in Crimea. Shown modern problems of geological training bases. Proposals for their development.